Determination and analysis of the complete genome sequences of a vaccine strain and field isolate of Lumpy Skin Disease Virus (LSDV) - Nel, Louis Hendrik (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2003.